The political economy of foreign aid: allocation, timing, and effectivenes - Eichenauer, Vera (2016)
This thesis consists of four essays on the political economy of foreign aid. These essays cover issues related to the allocation, the timing, and the economic consequences of foreign aid for recipient countries. Chapters 1 and 3 consider the allocation of official development assistance across different aid channels (bilateral, multi-bi/trust funds, or multilateral). Chapter 2 studies the sub-annual timing of aid contributions to World Bank funds. Chapter 4 examines the growth consequences of short-term politically motivated foreign aid.
Keywords: Hochschulschrift; Internationale Kooperation; Politische Wissenschaft; Politische Ökonomie